Direct On-Lay Repair of Isolated Pediatric Lateral Collateral Ligament Knee Injury with Biceps Femoris Tendon Rotation Graft Augmentation: A Case Report. Issue 1 (26th January 2022) - Perry, Samuel; Matelic, Thomas; Beyer, Sean
Abstract : Case: A 13-year-old male American football player sustained an isolated grade III lateral collateral ligament (LCL) rupture and underwent direct repair with biceps femoris rotation graft augmentation after failure of nonoperative management. The procedure was performed without any complications or graft site morbidity and achieved complete functional resolution. Conclusion: Isolated LCL injuries in the pediatric population are an extremely rare finding, with no evidence of rotation graft in the literature to date. Most of these cases involve multiligamentous knee injuries in the adult population, and therefore, there is no consensus regarding pediatric repair vs. reconstruction in this presentation.